2012
DOI: 10.1111/j.1365-2605.2012.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between chemical pattern in breast milk and congenital cryptorchidism: modelling of complex human exposures

Abstract: During the past four decades, there has been an increase in the incidence rate of male reproductive disorders in some, but not all, Western countries. The observed increase in the prevalence of male reproductive disorders is suspected to be ascribable to environmental factors as the increase has been too rapid to be explained by genetics alone. To study the association between complex chemical exposures of humans and congenital cryptorchidism, the most common malformation of the male genitalia, we measured 121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…In our network, HCB is predicted to be associated with reproductive disorders such as congenital malformation and abnormal sperm. Environmental exposure to endocrine disrupting chemicals, including HCB, have been suggested as a risk factor for male genital abnormalities such as hypospadias (Rignell-Hydbom et al, 2012;Krysiak-Baltyn et al, 2012). A recent study showed for the first time a correlation between serum concentration of HCB and semen quality (Paoli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In our network, HCB is predicted to be associated with reproductive disorders such as congenital malformation and abnormal sperm. Environmental exposure to endocrine disrupting chemicals, including HCB, have been suggested as a risk factor for male genital abnormalities such as hypospadias (Rignell-Hydbom et al, 2012;Krysiak-Baltyn et al, 2012). A recent study showed for the first time a correlation between serum concentration of HCB and semen quality (Paoli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the research is highly uncertain, there are strong indications that similar patterns of critical temporal vulnerabilities are present in all "wildlife" categories addressed by Kortenkamp et al (2011), i.e., other mammals, birds, fish, and invertebrates. In addition, EDC scientists as well as researchers developing new technologies for the monitoring and assessment of hormonally active substances have identified serious environmental consequences from releasing them into the environment (Hyötyläinen and Riekkola 2007, Kortenkamp et al 2011, Krysiak-Baltyn et al 2012. Finally, recent research on EDCs has demonstrated that geographical differences matter.…”
Section: The Regulation Of Endocrine-disrupting Chemicals In the Euromentioning
confidence: 99%
“…Finally, recent research on EDCs has demonstrated that geographical differences matter. Whether or not adverse effects will occur depends not only on the specific compounds found in a particular area, but on the specific mixtures these compounds happen to form as a result of agriculture, industry, and consumption patterns (Krysiak-Baltyn et al 2012).…”
Section: The Regulation Of Endocrine-disrupting Chemicals In the Euromentioning
confidence: 99%
“…To test the hypothesis, we measured more than one hundred toxicants in placentas and breast milk of mothers of boys with and without cryptorchidism in both Denmark and Finland to estimate the amount of prenatal exposure to endocrine disruptors [14,15,16,17,18,19], including 17 dioxin, 37 PCB, and 14 PBDE congeners. Dioxins, and dioxin-like PCBs, are well-known toxicants that exert most of their endocrine effects through aryl hydrocarbon receptors (AhR) that may interact with many other transcription factors [20].…”
Section: Case Study: Association Between Cryptorchidism and Dioxins Amentioning
confidence: 99%
“…Although the PCBs have not been produced in large scale after the 1980s [1] and the production and circulation of PCBs, dioxins, and most PBDE congeners was planned to be stopped under the Stockholm Convention [23] due to their chemical properties, they are still present in fauna even in remote locations such as Svalbard in the Arctic Ocean [24]. In the Danish-Finnish birth cohort study, exposures were measured in breast milk collected over a 2-month period starting at 1 month after delivery [14,17,25]. After each feeding when the baby was satisfied, the mother collected some of the remaining milk in a cup that was emptied in a glass bottle that was stored in the freezer.…”
Section: Case Study: Association Between Cryptorchidism and Dioxins Amentioning
confidence: 99%